(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Digital transformation has forced Suara.com, one of Indonesia’s leading online media platforms, to undergo profound organizational restructuring to survive algorithmic disruption and the pressures of digital capitalism. This study aims to analyze Suara.com’s structural dynamics through the perspective of Anthony Giddens’ Structuration Theory, focusing on the interaction between "rules" and "resources" as elements of a non-physical, flexible, and evolving organizational structure. Using a qualitative approach, this study collected data through in-depth interviews with key editorial and managerial staff, supported by content analysis, non-participant observation, and document review. The findings reveal that Suara.com integrates the roles of a media organization with those of a digital agency, a community network coordinator, and an event organizer. While editorial autonomy serves as a key authoritative resource, financial needs have driven a diversification strategy that risks blurring the boundaries between journalism and commercial interests. The study concludes that Suara.com’s structural flexibility reflects a capacity for adaptability and compromise, where journalistic ideals are continually negotiated under the shadow of market logic and algorithmic dominance.